2021
DOI: 10.2147/dddt.s334518
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IRF2 Alleviates Sepsis-Related Acute Kidney Injury in vitro and in vivo

Abstract: Objective:We investigated the roles and mechanisms of IRF2 in sepsis-related acute kidney injury (S-AKI) in a lipopolysaccharide (LPS)-induced HK-2 cell line and caecal ligation and puncture (CLP)-induced IRF2 −/− mouse model. Methods: Quantitative real-time polymerase chain reaction assay was used to detect IRF2 in the serum of S-AKI patients and LPS-induced HK-2 cells. Cell proliferation, death, and apoptosis were analysed by CCK-8, lactate dehydrogenase release, and flow cytometry assays, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Guo et al ( 115 ) and Liu et al ( 116 ) found that apoptosis and pyroptosis coexist in CLP mice. Li and Liu confirmed the same results ( 117 , 118 ). Yu et al ( 108 ) found that autophagy existed in a CLP mouse model, in the early stage, autophagy was stronger, and gradually weakened over time.…”
Section: Relationship Between Various Types Programmed Cell Deathsupporting
confidence: 73%
“…Guo et al ( 115 ) and Liu et al ( 116 ) found that apoptosis and pyroptosis coexist in CLP mice. Li and Liu confirmed the same results ( 117 , 118 ). Yu et al ( 108 ) found that autophagy existed in a CLP mouse model, in the early stage, autophagy was stronger, and gradually weakened over time.…”
Section: Relationship Between Various Types Programmed Cell Deathsupporting
confidence: 73%
“…In cellular experiments, Zhang et al found that LPS can increase TNF-α and IL-1β expression in HK-2 cells [23]. In this study, HK-2 cells were treated with 10 µg/ml LPS, and TNF-α and IL-1β expression was increased, confrming that LPS can induce infammatory damage in HK-2 cells.…”
Section: Discussionsupporting
confidence: 50%
“…There are only two studies reporting this. Zhang et al found that downregulated IRF2 could alleviate S-AKI in vitro and in vivo [ 36 ]. Liu and Wang found that the DRP1 inhibitor could alleviate LPS-reduced S-AKI by inhibiting NLRP3 inflammasome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%